2019
DOI: 10.1200/jco.2019.37.15_suppl.e15081
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of somatic mutations in the KRAS gene in patients of the South Russia diagnosed with colorectal cancer.

Abstract: e15081 Background: Colorectal cancer (CRC) is a common pathology in the world; the annual incidence rate reaches 1 million cases, and the annual mortality rate exceeds 500,000. The target therapy of EGFR with monoclonal drugs improves the survival of patients with this pathology. However, the effectiveness of therapy depends on the presence of mutations in genes involved in the EGFR signaling cascade, in particular KRAS. The purpose of this study was to determine the frequency of somatic mutations in the KRAS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…The frequency of KRAS mutations (exon 2 and exon 3) in our cohort reached 61.88%. This was much higher than what was reported in the Asia-Pacific (37-52%) and Western populations (32-49%) [25][26][27][28][29][30][31][32][33][34][35][36][37][38]. Nevertheless, our data is in line with a previous study in Indonesia, showing that KRAS mutation was found in 71.8% of serrated adenocarcinoma (SA), which is intriguingly higher than the generally reported incidence of 40% [39][40][41].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The frequency of KRAS mutations (exon 2 and exon 3) in our cohort reached 61.88%. This was much higher than what was reported in the Asia-Pacific (37-52%) and Western populations (32-49%) [25][26][27][28][29][30][31][32][33][34][35][36][37][38]. Nevertheless, our data is in line with a previous study in Indonesia, showing that KRAS mutation was found in 71.8% of serrated adenocarcinoma (SA), which is intriguingly higher than the generally reported incidence of 40% [39][40][41].…”
Section: Discussionsupporting
confidence: 83%
“…Colorectal cancer (CRC) is the third most prevalent cancer worldwide and as well as one of the most deadly. Approximately in Indonesia, over 35,000 patients are diagnosed with CRC each year [1].…”
Section: Introductionmentioning
confidence: 99%